Effects of Dietary Nitrate Supplementation on Physiological Responses, Cognitive Function, and Exercise Performance at Moderate and Very-High Simulated Altitude - Shannon, Oliver M.; Duckworth, Lauren; Barlow, Matthew J.; Deighton, Kevin; Matu, Jamie; Williams, Emily L.; Woods, David; Xie, Long; Stephan, Blossom C. M.; Siervo, Mario; O'Hara, John P. (Frontiers in Physiology, 2017)
Purpose: Nitric oxide (NO) bioavailability is reduced during acute altitude exposure, contributing toward the decline in physiological and cognitive function in this environment. This study evaluated the effects of nitrate (NO3−) supplementation on NO bioavailability, physiological and cognitive function, and exercise performance at moderate and very-high simulated altitude. Methods:Ten males (mean (SD): V˙O2max: 60.9 (10.1) ml·kg−1·min−1) rested and performed exercise twice at moderate (~14.0% O2; ~3,000 m) and twice at very-high (~11.7% O2; ~4,300 m) simulated altitude. Participants ingested either 140 ml concentrated NO3−-rich (BRJ; ~12.5 mmol NO3−) or NO3−-deplete (PLA; 0.01 mmol NO3−) beetroot juice 2 h before each trial. Participants rested for 45 min in normobaric hypoxia prior to completing an exercise task. Exercise comprised a 45 min walk at 30% V˙O2max and a 3 km time-trial (TT), both conducted on a treadmill at a 10% gradient whilst carrying a 10 kg backpack to simulate altitude hiking. Plasma nitrite concentration ([NO2−]), peripheral oxygen saturation (SpO2), pulmonary oxygen uptake (V˙O2), muscle and cerebral oxygenation, and cognitive function were measured throughout. Results: Pre-exercise plasma [NO2−] was significantly elevated in BRJ compared with PLA (p = 0.001). Pulmonary V˙O2 was reduced (p = 0.020), and SpO2 was elevated (p = 0.005) during steady-state exercise in BRJ compared with PLA, with similar effects at both altitudes. BRJ supplementation enhanced 3 km TT performance relative to PLA by 3.8% [1,653.9 (261.3) vs. 1718.7 (213.0) s] and 4.2% [1,809.8 (262.0) vs. 1,889.1 (203.9) s] at 3,000 and 4,300 m, respectively (p = 0.019). Oxygenation of the gastrocnemius was elevated during the TT consequent to BRJ (p = 0.011). The number of false alarms during the Rapid Visual Information Processing Task tended to be lower with BRJ compared with PLA prior to altitude exposure (p = 0.056). Performance in all other cognitive tasks did not differ significantly between BRJ and PLA at any measurement point (p ≥ 0.141). Conclusion: This study suggests that BRJ improves physiological function and exercise performance, but not cognitive function, at simulated moderate and very-high altitude.